Psykoanalysens poetik - Gammelgaard, Judy (Psyke & Logos, 2023)
In this article the author opens a discussion on Freud' s ideas of a psychoanalytic theory of aesthetics. The discussion is primarily concentrated on two of Freud's literary analyses: Wilhelm Jensen's novel Gradiva from 1907 and E.T.A. Hoffmann's story about the Sandman from 1919. The author points out the problem that Freud's aesthetic analyses almost all have their roots in his earlier writings, i.e. before the introduction of the structural model and the revised theory of instinct. This means that the Pleasure principle and the Wish-fulfilment theory originating from the work of dream interpretation are the thematic premises behind Freud' s thoughts about art and creativity. This hedonistic point of view has not without reason been criticized for reducing the rich complexity of art. With the reformulation of the theory of instinct and the introduction of Repetition compulsion a shift in perspective is accomplished in what could be called the aesthetics of psychoanalysis. Emphasized is the suggestion of this reformulation in the article from 1919 about Das Unheimliche in which the analysis of the Sandman is part. The author finally suggests a continued discussion implying a clarification of the concept of sublimation so vital to psychoanalytical poetics.